Development of Learning Media E-Booklet Science Literacy Based Improving Students' Critical Thinking Ability on Immune System Materials - Aprilia Serephina Gultom; Rita Retnowati; Indri Yani (Journal Of Biology Education Research (JBER), 2022)
The material on the immune system is one of the most difficult materials for students. In view of this, the use of technology as a medium of learning on immune system material is one way to help students apply the scientific process by building students' critical thinking levels. This study aims to develop and analyze the application learning media -e-booklet of scientific literacy based to be effective and able to improve students' critical thinking skills on immune system material. The research method used is Research and Development using the model FourD. This research was carried out in January-October 2021. The subjects of this study were students of class XI MIPA 4 in one of the public high schools in Bogor Regency for the academic year 2020/2021 as many as 36 students. The field trial was conducted in a limited manner using a research design one group pretest-posttest. The results showed that the learning media -e-booklet scientific literacy based developed had a very valid/feasible category with a percentage of 83.2%. For the feasibility test, three media and materials experts and two high school biology teachers were used. Critical thinking questions that have been validated also have a very valid category with an index of 0.83. The Learning media is -e-booklet scientific literacy based also able to improve students' critical thinking skills from moderate to high levels with a percentage of 38.00% and an average n-gain of 0.66.